Hubungan kualitas tidur dengan perkembangan bayi usia 3-10 bulan - Suryati Suryati; Eka Oktavianto (Health Sciences and Pharmacy Journal, 2020)
The brain in a baby grows 3 times the state at birth or 80% of an adult brain in its first year. This condition only happens once in a life time. So that for maximum growth and development, babies need adequate sleep. Sleep disorders in children can have an impact, both on aspects of physical growth, as well as cognitive, emotional, social and child behavior. This study is aimed to determine the relationship between sleep quality and the development of infants aged 3-10 months in the village of Tamanan Banguntapan II Primary Health Center. Descriptive correlation with cross sectional approach was conducted. Chi square test was performed. The number of samples in this study were 36 infants aged 3-10 months. Purposive sampling was used as sample taking technique. A Brief Screening Questionnaire for Infant Sleep Problems (BISQ) and the Denver Developmental Screening Test (DDST II) sheet was used as data collection tools. Statistical test results showed that the value of p=0,001 (p value